Effect of Sex and Age Differences on Premature Ventricular Ectopic Beats in Apparently Normal Hearts - Miqdam M. Obaid Al-Jumaili; Mohammed A. Ajeel; Wijdan I.A. Abd-Alwahab (Institute of Medico-legal Publications Pvt Ltd, 2021)
Ventricular ectopic beat (VEB) is a common cause in clinical practice. sometimes this case is asymptomaticbut can cause uncomfortable symptoms in patients. There are some cases where the VEBs presence indicatesa risk factor towards severe arrhythmias, especially when associated with normal hart. Normal cases thatusually encounter episodes of ectopic beats were collected (58 individuals 23 were females and the rest (34)were males) from the private consultative clinic or from the Sherqat general Hospital attendance in Salahal-Din Governorate whose ages ranged between 38-66. These cases were followed up closely for two yearswith a clinical examination every 3 months with electrocardiogram Heart, chest x-ray, echocardiography.Regarding the management strategies (Table 2), 36 patients (19 males and 11 females) (49%) were satisfiedby B-Blocker 19 of them (33%) were less than 60 years and 9 were equal or above the 60. Thirteen of theparticipants (23%) were given reassurance 3 of them (5%) were less than 60 years and 10 were equal orabove 60. Nine individuals (16%) cases responded to simple sedativezers) 5 of them (9%) were less than 60years and 9 were equal or above 60. 7 (12%) were treated by a combination of sedative and prokinetics 6of the cases (9%) were less than 60 years and 9 were equal or above 60. Electrocardiographic and CardiacElectrophysiological Properties of the study (Table 3) shows that 33 individuals (40%) were unifocal) wereunifocal premature Ventricular ectopic beats their age were under 60 for all of them. The rest (24) weremultifocal type. The QRS were significantly longer in male than in female and in the =60 more than that ofthe <60. In this regard, the result demonstrates that predominant S wave in 15 male participants versus 12females. While there was 19 male having dominant R wave. Sex and age have a significant impact on cardiacelectrophysiological characteristics of Premature Ventricular ectopic beats.The males are more affected with Premature Ventricular ectopic beats than females regarding this effect.